Complementary and alternative medicine and musculoskeletal pain in the first year of adjuvant aromatase inhibitor treatment in early breast cancer patients. (April 2020) - Hack, C.C.; Häberle, L.; Brucker, S.Y.; Janni, W.; Volz, B.; Loehberg, C.R.; Hartkopf, A.D.; Walter, C.-B.; Baake, G.; Fridman, A.; Malter, W.; Wuerstlein, R.; et al.
Abstract: Background: Patients with breast cancer (BC) show strong interest in complementary and alternative medicine (CAM), particularly for adverse effects of adjuvant endocrine treatment — e.g., with letrozole. Letrozole often induces myalgia/limb pain and arthralgia, with potential noncompliance and treatment termination. This analysis investigated whether CAM before aromatase inhibitor (AI) therapy is associated with pain development and the intensity of AI-induced musculoskeletal syndrome (AIMSS) during the first year of treatment. Patients and methods: The multicenter phase IV PreFace study evaluated letrozole therapy in postmenopausal, hormone receptor–positive patients with early BC. Patients were asked about CAM use before, 6 months after, and 12 months after treatment started. They recorded pain every month for 1 year in a diary including questions about pain and numeric pain rating scales. Data were analyzed for patients who provided pain information for all time points. Results: Of 1396 patients included, 901 (64.5%) had used CAM before AI treatment. Throughout the observation period, patients with CAM before AI treatment had higher pain values, for both myalgia/limb pain and arthralgia, than non-users. Pain increased significantly in both groups over time, with the largest increase during the first 6 months. No significant difference of pain increase was noted regarding CAM use. Conclusions: CAM use does not prevent or improve the development of AIMSS. Pain intensity was generally greater in the CAM group. Therefore, because of the risk of non-compliance and treatment discontinuation due to the development of higher pain levels, special attention must be paid to patient education and aftercare in these patients. Highlights: Pain levels of myalgia/limb pain and arthralgia increase under letrozole intake. Within one year pain levels increase in both, CAM users as well as non-CAM users. In CAM users pain levels were higher at all time points than in non-CAM users. The greatest increase of pain levels was noted in the first six treatment months. CAM does not prevent or improve the development of myalgia/limb pain and arthralgia.